TEVAR for complicated and uncomplicated type B aortic dissection—Systematic review and meta‐analysis. Issue 10 (26th July 2021) - Howard, Callum; Sheridan, Jonathan; Picca, Leonardo; Reza, Sihab; Smith, Tristan; Ponnapalli, Anuradha; Calow, Rachel; Cross, Olivia; Iddawela, Sashini; George, Melvin; Livra Dias, Deidre; Srinivasan, Anand; et al.
Abstract: Background: Type B aortic dissection (TBAD), is defined as a dissection involving the aorta distal to left subclavian artery with the ascending aorta and the aortic arch not affected. TBAD is classified due to the time frame and presence of complications. Complicated TBAD (co‐TBAD) patients have a greater mortality rate than uncomplicated TBAD (un‐TBAD) and thoracic endovascular aortic repair (TEVAR) is considered the gold‐standard intervention for these clinical challenges. Methods: We undertook a systematic review of the literature regarding TEVAR intervention in co‐TBAD and un‐TBAD. A comprehensive search was undertaken across four major databases and was evaluated and assessed until June 2020. Results: A total of 16, 104 patients were included in the study (7772 patients co‐TBAD and 8352 un‐TBAD). A significantly higher proportion of comorbidities were seen in co‐TBAD patients compared with un‐TBAD. Acute dissection was more frequent in the co‐TBAD group (73.55% vs. 66.91%), while chronic dissection was more common in un‐TBAD patients (33.8% vs. 70.73%). Postprocedure stroke was higher in co‐TBAD (5.85% vs. 3.92%; p < .01), while postprocedural renal failure was higher in un‐TBAD patients (7.23 vs. 11.38%; p < .01). No difference was observed in in‐hospital mortality however the 30 days mortality was higher in the co‐TBAD group. One‐year survival was higher in the uncomplicated group but this difference was not observed in the 5‐year survival. Conclusion: In our analysis we can appreciate that despite significantly higher comorbidities in the co‐TBAD cohort, there was no difference in in‐hospital mortality between the two groups and the 5‐year survival did not have any difference.